Driving Adoption of Islamic Wealth Accumulation Products: The Impact of Financial Literacy, Information Technology, Cost and Benefit among Corporate Customers In Pakistan - Muhammad Faheem Arshad; Lim Chee Chee; Zunarni Kosim (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
This research aims to assess the influence of Islamic financial literacy, information technology and intentions to adopt Islamic wealth accumulation products, and the moderating effect of cost and benefit on the relationship between Islamic financial literacy, information technology and intentions to adopt Islamic wealth accumulation products. The data was collected from 395 corporate customers in major cities of Pakistan. The research employed a quantitative approach and analysed the data using structural equation modelling through SmartPLS. The outcomes of the research indicate that Islamic financial literacy and information technology have a significant positive effect on the adoption of Islamic wealth accumulation products. The study also found that cost and benefit play a significant moderating role in the relationship between the Islamic financial literacy, information technology and intentions to adopt Islamic wealth accumulation products. Based on the findings, it is recommended that financial institutions should focus on increasing Islamic financial literacy and providing advanced information technology to corporate customers to boost their intentions to adopt Islamic wealth accumulation products. Furthermore, the research emphasizes the need to consider the perceived cost and benefit of the product when designing effective marketing strategies to promote the adoption of Islamic wealth accumulation products. The outcomes of this research can assist financial institutions in comprehending the factors that impact the adoption of Islamic wealth accumulation products among corporate customers in Pakistan and developing effective marketing strategies to encourage their adoption.